An Integrated Cross Layer Design to Enhance the Quality of Service of Video Streaming in Mobile Adhoc Networks - N. Gomathi; M. Uvaneshwari (International Journal of Informatics and Communication Technology (IJ-ICT), 2018)
The intent of this paper is to put forth a novel technique for improvising the QoS of multimedia applications in by using Modified dynamic mapping algorithm and Multipath transport(MPT) and Multi Description Coding(MDC). The improvement is attained by applying the MDC at application layer along with UDPLite in transport layer and multipath at network layer and Modified dynamic mapping in MAC Layer.Thismethod attains an increase of 30.84% in Peak Signal to Noise Ratio (PSNR) and 18.57% decrease in delay in contrast to the conventional methods.